(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
This study evaluates the role of Apulia as a cultural crossroads and trade centre during the Middle Ages, as a consequence of its strategic position between the eastern Mediterranean and the Adriatic. The region’s prominence in trade is evidenced by the import of Byzantine and Arab ceramics under the Byzantine Empire and until the Norman conquest. With the formation of the Latin Empire of Constantinople, Apulian ceramic production, in particular Brindisi protomaiolica and glazed ceramics produced in Lecce, Taranto and the Ionian area, became the dominant form of pottery in the markets of Frankish Greece and the Crusader states in the Levant. The research focuses on the production and trade of Apulian ceramics between the 12th and 15th centuries. It demonstrates a notable shift in the composition of imports, accompanied by a surge in local production, which was shaped by the influence of Byzantine and Arab ceramics. During the 13th century, Apulia developed a multitude of ceramic production centres in order to meet the demands of the internal and external markets, exporting to Italy, Greece, and the Levant. From the fifteenth century onwards, the Ottoman occupation of the Balkans resulted in a contraction of trade. However, Apulian production adapted, focusing on the domestic markets and those of central and northern Italy. Active trade networks along the Adriatic coast were maintained until the modern age.